Utilization of Liveworksheets based Interactive Student Worksheets to Improve Junior High School Students' Learning Outcomes in Writing Explanatory Texts - Dyajeng Ayu Permatasari; I Wayan Rasna; Ida Ayu Made Darmayanti (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The lack of innovative learning media has resulted in low learning outcomes for ninth-grade students in writing explanatory texts, characterized by low student motivation and engagement in conventional worksheet-based writing lessons. This creates a gap between the expectations of the Independent Curriculum, which emphasizes scientific writing skills with good structure and logic, and the reality in the classroom. This study aims to analyze the use of interactive worksheets based on Liveworksheets in improving writing learning outcomes, as well as exploring changes in student motivation and responses. A two-cycle classroom action research with 38 students as subjects, used observations, writing tests, motivation questionnaires, and interviews as data collection instruments. Data analysis was conducted quantitatively and qualitatively. A comparison of learning outcomes between Cycle I and Cycle II showed improvement for each student. Students who previously obtained a score of 61 (adequate) in cycle I increased to 89 (very good) in cycle II. The increase in the average score of 13.3 points (from 67.4 to 80.7) confirms that the corrective actions taken were effective in improving student learning outcomes. The research results show that interactive media is effective in closing the learning gap and supporting 21st-century writing skills. The implications of this research can be used as a basis for curriculum development and teacher training on a broader scale.